2014
DOI: 10.1002/dvg.22750
|View full text |Cite
|
Sign up to set email alerts
|

Sea urchin neural development and the metazoan paradigm of neurogenesis

Abstract: Summary: Urchin embryos continue to prove useful as a means of studying embryonic signaling and gene regulatory networks, which together control early development. Recent progress in understanding the molecular mechanisms underlying the patterning of ectoderm has renewed interest in urchin neurogenesis. We have employed an emerging model of neurogenesis that appears to be broadly shared by metazoans as a framework for this review. We use the model to provide context and summarize what is known about neurogenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 84 publications
(172 reference statements)
1
37
0
Order By: Relevance
“…Although there are significant differences in the nervous systems created from this early territory among the deuterostomes, the ANE initially arises from a relatively simple, flat neuroepithelium during the early stages of development and many of the cell types that this territory produces are remarkably conserved (Burke et al, 2014;Castro et al, 2015;Cavodeassi, 2013;Garner et al, 2015;Pani et al, 2012;Range, 2014). Based on the spatial and temporal expression of ANE regulatory genes in several species, it appears that the ANE gene regulatory network (GRN) hierarchy is also remarkably conserved among many deuterostome embryos, suggesting that these could be homologous territories (Range, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Although there are significant differences in the nervous systems created from this early territory among the deuterostomes, the ANE initially arises from a relatively simple, flat neuroepithelium during the early stages of development and many of the cell types that this territory produces are remarkably conserved (Burke et al, 2014;Castro et al, 2015;Cavodeassi, 2013;Garner et al, 2015;Pani et al, 2012;Range, 2014). Based on the spatial and temporal expression of ANE regulatory genes in several species, it appears that the ANE gene regulatory network (GRN) hierarchy is also remarkably conserved among many deuterostome embryos, suggesting that these could be homologous territories (Range, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Simultaneous hybridization with probes for Hnf6 (also known as onecut), which is an APD/ ciliary band marker, and SoxC transcripts showed that SoxCexpressing cells lie adjacent to, or within, the ciliary band and APD ( Fig. 1G-I′, arrowheads), as expected for neural precursors (Burke et al, 2014). Further supporting this identity, cells in both the apical plate and lateral ectoderm that express SoxC also express Delta (Fig.…”
Section: Soxc Function Is Required Downstream Of Six3 For Developmentmentioning
confidence: 57%
“…At the end of embryogenesis the nervous system of the sea urchin early pluteus larva includes an apical ganglion in the apical plate at the anterior (animal) pole, a set of 40-50 peripheral neurons, most of which differentiate in, or adjacent to, the ciliary band, and a few neurons that differentiate in the pharyngeal endoderm Wei et al, 2009;Range et al, 2013;Burke et al, 2014) (Fig. S1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…SoxB genes have been associated with broad neurogenic functions throughout the animal kingdom, from deuterostomes (chordates, echinoderms, hemichordates) (Burke et al, 2014;Reiprich and Wegner, 2014;Taguchi et al, 2002) and protostomes (Ecdysozoa, Lophotrochozoa) (Kerner et al, 2009;Overton et al, 2002) to even earlier diverging animal lineages such as cnidarians (Richards and Rentzsch, 2014). SoxB proteins are required for neuronal commitment broadly throughout the embryonic nervous system during the earliest stages of development, predominantly in proliferating, undifferentiated precursors (Pevny and Placzek, 2005;Pevny and Nicolis, 2010;Reiprich and Wegner, 2014;Sarkar and Hochedlinger, 2013).…”
Section: Discussionmentioning
confidence: 99%